Scaling‐up camera traps: monitoring the planet's biodiversity with networks of remote sensors. Issue 1 (20th December 2016) - Steenweg, Robin; Hebblewhite, Mark; Kays, Roland; Ahumada, Jorge; Fisher, Jason T; Burton, Cole; Townsend, Susan E; Carbone, Chris; Rowcliffe, J Marcus; Whittington, Jesse; Brodie, Jedediah; Royle, J Andrew; et al.
Abstract : Countries committed to implementing the Convention on Biological Diversity's 2011–2020 strategic plan need effective tools to monitor global trends in biodiversity. Remote cameras are a rapidly growing technology that has great potential to transform global monitoring for terrestrial biodiversity and can be an important contributor to the call for measuring Essential Biodiversity Variables. Recent advances in camera technology and methods enable researchers to estimate changes in abundance and distribution for entire communities of animals and to identify global drivers of biodiversity trends. We suggest that interconnected networks of remote cameras will soon monitor biodiversity at a global scale, help answer pressing ecological questions, and guide conservation policy. This global network will require greater collaboration among remote‐camera studies and citizen scientists, including standardized metadata, shared protocols, and security measures to protect records about sensitive species. With modest investment in infrastructure, and continued innovation, synthesis, and collaboration, we envision a global network of remote cameras that not only provides real‐time biodiversity data but also serves to connect people with nature.